IMPROVEMENT OF PHONEMATIC HEARING IN THE SYSTEM OF EXTERNAL SPEECH TECHNIQUE OF ACTORS - Anfisa Kolenko ("Scientific Information Agency "Science-technologies-information" LLC, 2020)
Phonemic hearing is a type of hearing that is the basis for understanding the meaning of what is said. In working with future actors to improve the skills of phonemic hearing in the system of speech technique should use a game form of learning. For example: to identify extraneous sounds (noises) coming to the hearing organs of actors both with visual support and without it, with open and closed eyes; to identify the sounds made by musical instruments both with and without visual support; to identify non-speech sounds produced by actors.